Analysis of Item Difficulty and Student Misconceptions on Temperature and Heat Using a Two-Tier Diagnostic Test - Royani, Shinta Nuriyah Mahbubiyah; Artanti, Kafa Pramitha Indhira Anggraini; Putri, Rafa' Anugrah; Parno, Parno (Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aimed to analyze the level of problem difficulty and students’ misconceptions on the topic of temperature and heat using a two-tier diagnostic test. A two-tier diagnostic test was administered to a sample of undergraduate physics education students at three major universities in East Java to assess their understanding of these basic physics concepts. The first tier of the test evaluated students’ ability to answer content-related questions correctly, while the second tier explored the reasoning behind their responses. Data were also collected on the Certainty Response Index (CRI) to determine students’ confidence levels in their answers. Data analysis was conducted to determine the problem's difficulty level and identify common misconceptions. The results showed students had difficulty solving problems at levels C3 and C4, especially on representation problems. These findings highlight the need for appropriate teaching strategies to address these misconceptions and improve students’ conceptual understanding of temperature and heat. This study provides valuable insights into assessing students’ knowledge and identifying key areas for instructional improvement in thermodynamics teaching.